Pengamanan Citra Grayscale menggunakan Penggabungan Kriptografi Visual Secret Sharing dan Steganografi Enhanced Least Significant Bit (Jurnal EurekaMatika, 2024)
The rapid advancement of technology has made the process of information exchange easier. However, this  convenience is often exploited by irresponsible parties to hack messages or confidential information. Cryptography and steganography are among the solutions to protect and enhance the security of messages or confidential information. One commonly used form of information is images. This study examines the combination of Visual Secret Sharing cryptography and Enhanced Least Significant Bit steganography in securing grayscale images. The image message is disguised into several parts using Visual Secret Sharing cryptography and then hidden in another image using Enhanced Least Significant Bit steganography. Enhanced Least Significant Bit is an improved method of the Least Significant Bit where the bits used for hiding the message are not the last LSB bits but last two or last three LSB bits. The results of the study show that this combination has a high level of security as it requires two data security techniques and the appropriate number of images to retrieve the disguised message.ABSTRAKPenelitian ini mengkaji tentang penggabungan kriptografi visual Secret Sharing dan steganografi Enhanced Least Significant Bit dalam mengamankan citra grayscale. Citra pesan disamarkan menjadi beberapa bagian dengan kriptografi visual Secret Sharing kemudian disembunyikan ke citra lain dengan steganografi Enhanced Least Significant Bit. Enhanced Least Significant Bit merupakan metode Least Significant Bit yang ditingkatkan di mana bit yang digunakan sebagai tempat penyembunyian pesan bukanlah bit LSB terakhir melainkan dua atau tiga bit LSB terakhir. Hasil penelitian menunjukkan bahwa penggabungan ini memiliki tingkat keamanan yang tinggi karena memerlukan dua teknik keamanan data dan banyak citra yang sesuai untuk mendapatkan pesan yang sudah disamarkan.
Keywords: Citra Grayscale; Enhanced LSB; Kriptografi Visual; Skema Secret Sharing; Steganografi